(untitled) (Law and world, 2016)
According to the EU-Georgia Association Agreement, article 354, Georgia took an obligation to carry out approximation of its legislation to the EU acts and international instruments, among other, regarding the labour law as well. This article discusses relevance of Georgian legislation to the EU requirements regarding the leave of an employee. At the same time comparative-legislative analysis of Georgian and German legislation regulating the leave issues is given in the article. The article concerns to the annual leave, as well as pregnancy, giving a birth and maternity leave issues.